MODIFICATION OF C-USLE FACTOR IN ANSWERS MODEL TO PREDICT SOIL EROSION IN HUMID TROPICAL REGION (CASE STUDY OF NOPU UPPER CATCHMENT, CENTRAL SULAWESI) - HIDAYAT, Y.; SINUKABAN, N.; PAWITAN, H.; MURTILAKSONO, K. (Balai Besar Penelitian dan Pengembangan Sumberdaya Lahan Pertanian, 2010)
The research was carried out: a) to define crop and management factors as input parameter of ANSWERS model, b) to establish an ANSWERS to PCRaster model to simulate land use changes and soil and water conservation techniques, and c) to study the impact of rainforest conversion towards surface runoff, soil erosion and nutrients losses. Surface runoff and soil erosion were measured daily on primary forest, secondary forest, open areas, maize, peanut, young cocoa, medium cocoa, old cocoa, and intercropping between young cacao, maize, banana, and cassavas. In watershed outlet, surface runoff and sediment discharges were determined through measurement of water height, velocities and sediment sampling. Using a partial crop and management factors, the original and PCRaster type of an ANSWERS model performs better in predicting soil erosion thanUSLE crop and management factors especially for high rainfall events. Reforestration of very steep land (slope > 45%) which followed by application of ridge terraces on agricultural areas were the best management practices to control surface runoff and soil erosion to ensure sustainable agriculture andsustainability of watershed functions. Rainforest conversion to agricultural areas increases surface runoff, soil erosion andnutrients losses.